2021
DOI: 10.1017/s0714980821000040
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Networking and Mental Health among Older Adults: A Scoping Review

Abstract: As the number of older adults is expected to increase exponentially within the next few decades, loneliness, social isolation, and depression among seniors are growing public health concerns. Although formal treatment options, such as therapy and medication, can be helpful for depression, they can also be expensive and sometimes ineffective. It is therefore important to consider other potential treatment options and social interventions. Alternative methods for addressing mental health issues are especially im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 99 publications
(210 reference statements)
0
29
0
Order By: Relevance
“…In sum, this study adds to the limited knowledge regarding the frequency of contact with friends and relatives via internet and psychosocial factors based on nationally representative data. 1 , 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In sum, this study adds to the limited knowledge regarding the frequency of contact with friends and relatives via internet and psychosocial factors based on nationally representative data. 1 , 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Similarly, only a few studies examined the association between contact with friends and relatives via internet and depressive symptoms as well as life satisfaction. 2 Another very recent scoping review identified positive associations between online social networking and life satisfaction, an enhanced communication with relatives and friends and decreased depressive symptoms. 2 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations